An investigation into the hydrothermal processing of coal fly ash to produce zeolite for controlled release fertiliser applications - Elliot, Alexander Dean (Curtin University, 2006)
During the year that concluded prior to the commencement of this PhD (2001) 11.7 million tonnes of fly ash was produced in Australia, of which only 32% was utilised is some way, near its conclusion, the latest statistics (2004), reveal that 12.5 million tonnes was produced with only 35% utilised in some way (ADAA 2006), with the remainder being accumulated in landfills and ash dams. This low level of ash utilisation in Australia is inevitable due to the combination of inherently high transport costs, and relatively low value products. This situation argues for more value-added utilisation of coal ash to overcome the transport cost barrier.Zeolite synthesised from fly ash for agricultural application as a controlled release fertiliser, is a technology which offers considerable advantages in terms of economic, technical and environmental performance. This fertiliser market is both a high value and high volume market, with the potential to consume significant quantities of fly ash. Studies using natural zeolite have demonstrated significant improvements in fertiliser efficiency for zeolite compared to soluble salts.This thesis looks at the issues behind fly ash utilisation in the broader sense, evaluates the potential markets for zeolite products in Australia, assesses the established science behind producing zeolite materials from fly ash, and examines the direct hydrothermal treatment process for producing zeolites (including analcime, cancrinite, zeolite ZK-14, and zeolite P1) from coal fly ash, including the relationship between zeolite types produced and operating conditions, desirable zeolite properties for controlled release fertilisers, optimal production conditions, economic implications, and avenues for future research.The hydrothermal treatment process was studied through the control of reaction temperature (T), reaction time (t), the Si/Al mole ratio (n), the cation type (M), the pH, the H2O/Al mole ratio (p), and the M+/Al mole ratio in excess of unity (m), where MNO3 was used to control m independent of pH. A number of different zeolite types were produced from fly ash with a maximum zeolite yield of 57%. Due to impurities present in the fly ash, it is impossible to selectively synthesise pure zeolite of any kind using the direct hydrothermal treatment method, but this is adequate for the intended fertiliser applications.A systematic quantitative refinement method was developed using Rietica to characterise the mineralogy of fly ash and hydrothermal treatment products, resulting in substantially more information regarding the transformations taking place than has previous been available in the study of the synthesis of zeolites from fly ash. This in conjunction with SEM has provided unprecedented detail regarding the reactivity of fly ash components, namely glass, quartz, and mullite phases, as well as the independent role of M+ and OH− within the hydrothermal system, and the encapsulation of fly ash reactants by products.Notably quartz is more reactive than mullite; however at a pH of 14.6 mullite is completely dissolved while quartz is not, probably due to the significantly smaller size of mullite crystals relative to quartz particles; and for small increases in m with constant pH starting from x = 1, the total yield of zeolite increases, and the yields of different zeolite types change from low to a maxima back to low as functions of both pH and m.From the experiments conducted it appears that the processes of gel formation and zeolite crystal growth can be manipulated through the continuous presence of zeolites with fly ash reactants, and through the manipulation and control of M+ and OH− concentrations as well as temperature to balance the suppression of fly ash dissolution while enhancing crystallisation to minimise the encapsulation of reactants by products, increasing the productivity of hydrothermal treatment process, therefore improve its economic viability, which is key to its possible future implementation.